Enhanced transfer hydrogenation of 2-heptanone to 2-heptanol over synergistic Co/ZnO catalysts - Dongpei Zhang; Jiefeng Liu; Sicheng Shao; Quanxing Zhang; Mengyuan Liu; Yuangao Wang; Mingyu Ma; Ning Cao; Guangyu Zhang; Jinyao Wang; Junwei Yang; Wenjuan Yan; et al. (Carbon Capture Science & Technology, 2024)
2-Heptanol is an important secondary alcohol, applied in food, pharmaceutical and plastic industries. However, current industrial synthetic methods require energy intensive hydrogenation of 2-heptanone using homogeneous noble catalysts in alkaline medium. In this work, we presented a systematic study on enhanced transfer hydrogenation of 2-heptanone to 2-heptanol using non-noble Co/ZnO catalysts without alkaline promoters. The strong synergism of Co and ZnO contributes to formation of amorphous metallic Co species and electronically reconfigured CoO species, leading to a 20-fold activity enhancement at 180 °C and a TOF of 89.4 h−1 over Co0.09/ZnO-500 catalysts. Structure-dependency studies further revealed that, the lattice strain between Co and ZnO induced the generation of multi-phased Co/CoO/Co:ZnO interfaces, facilitating tandem H2 generation, spillover and activation of C=O bond (of 2-heptanone molecule), respectively. The insights of molecular catalysis on interface of amorphous Co/ZnO for enhanced C=O bond activation, provide fundamental understanding for transfer hydrogenation of various other ketones into valuable alcohols.